2019
DOI: 10.1038/s41467-019-09306-7
|View full text |Cite|
|
Sign up to set email alerts
|

Dispersal homogenizes communities via immigration even at low rates in a simplified synthetic bacterial metacommunity

Abstract: Selection and dispersal are ecological processes that have contrasting roles in the assembly of communities. Variable selection diversifies and strong dispersal homogenizes them. However, we do not know whether dispersal homogenizes communities directly via immigration or indirectly via weakening selection across habitats due to physical transfer of material, e.g., water mixing in aquatic ecosystems. Here we examine how dispersal homogenizes a simplified synthetic bacterial metacommunity, using a sequencing-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 42 publications
(48 reference statements)
5
38
0
Order By: Relevance
“…S1). Finally, we verified that the levels of noise determined in this study are similar to the variability recorded from technical replicate samples taken during our previous experiment where we used the same bacterial system and instrument with identical settings [17]…”
Section: Assembling and Monitoring The Synthetic Bacterial Communitiessupporting
confidence: 79%
“…S1). Finally, we verified that the levels of noise determined in this study are similar to the variability recorded from technical replicate samples taken during our previous experiment where we used the same bacterial system and instrument with identical settings [17]…”
Section: Assembling and Monitoring The Synthetic Bacterial Communitiessupporting
confidence: 79%
“…Microorganisms found in various sources, such as surface and groundwater supplies, act as inocula in drinking water systems ( Figure 6(a)) to propagate populations along the treatment procedure [99]. Microorganisms occurring on certain treatment systems, such as filters or reactor wall surfaces, can subsequently be released during or after processing [102] to the delivery units that depend on whether or not disinfection has occurred [103,104]. Bidirectional immigration amidst the water process and the biofilms on the inner pipe surface is feasible in the distribution network [105], which can further be elevated via stagnating the water [106].…”
Section: Quantifying the Contribution Of Microbial Immigration In Ecomentioning
confidence: 99%
“…Our results revealed that microbial communities of water, shrimp intestine and sediment habitats in the SCPE had close relationships as communities of three habitats are connected to each other by various biological and ecological processes, including nutrient share, dispersal and microbial interactions [35,46,47]. For instance, dispersal is a key factor influencing the metacommunity and its associated community structure [48]. In this study, we observed that a high percentage of dispersal rates from sediment to the other two habitats in the SCPE, and especially, compared with water communities, shrimp intestine communities were more closely related to sediment communities.…”
Section: Discussionmentioning
confidence: 75%